Coupling between skeletal muscle fiber size and capillarization is maintained during healthy aging. Issue 4 (5th April 2017) - Barnouin, Yoann; McPhee, Jamie S.; Butler‐Browne, Gillian; Bosutti, Alessandra; De Vito, Giuseppe; Jones, David A.; Narici, Marco; Behin, Anthony; Hogrel, Jean‐Yves; Degens, Hans
Abstract: Background: As muscle capillarization is related to the oxidative capacity of the muscle and the size of muscle fibres, capillary rarefaction may contribute to sarcopenia and functional impairment in older adults. Therefore, it is important to assess how ageing affects muscle capillarization and the interrelationship between fibre capillary supply with the oxidative capacity and size of the fibres. Methods: Muscle biopsies from healthy recreationally active young (22 years; 14 men and 5 women) and older (74 years; 22 men and 6 women) people were assessed for muscle capillarization and the distribution of capillaries with the method of capillary domains. Oxidative capacity of muscle fibres was assessed with quantitative histochemistry for succinate dehydrogenase (SDH) activity. Results: There was no significant age‐related reduction in muscle fibre oxidative capacity. Despite 18% type II fibre atrophy ( P = 0.019) and 23% fewer capillaries per fibre ( P < 0.002) in the old people, there was no significant difference in capillary distribution between young and old people, irrespective of sex. The capillary supply to a fibre was primarily determined by fibre size and only to a small extent by oxidative capacity, irrespective of age and sex. Based on SDH, the maximal oxygen consumption supported by a capillary did not differ significantly between young and old people. Conclusions: The similar quantitative and qualitative distribution of capillaries within muscle from healthy recreationally active older people and young adults indicates that the age‐related capillary rarefaction, which does occur, nevertheless maintains the coupling between skeletal muscle fibre size and capillarization during healthy ageing.